DESIGN OF FIXED-DOME CHINESE TYPE BIOGAS REACTOR IN TREATMENT OF MANURE WASTES: A TYPICAL APPLICATION - Enturk, Emel; Yetilmezsoy, Kaan; Ozturk, Mustafa (YILDIZ TECHNICAL UNIV, 2006)
In this study, feasibility of a small-scale biogas plant in treatment of manure wastes was investigated for a poultry farm selected as a model pilot plant in Corum City. A fixed-dome Chinese type biogas reactor was proposed as an appropriate digestion process in treatment of manure wastes and calculations based on design criteria and literature data were presented.
Keywords: Biogas plant; fixed-dome reactor; manure; animal wastes; Engineering